The Role Of Selected Human Resource Policies On Job Satisfaction Of Female Employees In The Indian Hotel Industry - Himali Lakhera, Dr.Mahesh Uniyal, Dr. Neeraj Aggrawal, Anil Lakhera (International Journal of Advanced Science and Technology, 2020)
Past research shows significant links between various human resource policies and the overall job satisfaction of employees in hotels. However, the role of human resource policies on the job satisfaction of female employees in the Indian hotels remains relatively unexplored. The objective of this study is to investigate the role of selected HR Policies related to variables such as work condition, Safety & security and work life Balance on job satisfaction of female employees with reference to Indian Hotel Industry. The sample size of 50 female employees was taken into consideration to study through convenience sampling methods .The study was restricted to 05 hotels of 5* or 5*deluxe category of New Delhi region. Keywords: HR policies, Job Satisfaction, Female Employees, Hotel Industry, India, New Delhi region.